On a conditioned Limit Structure of the Markov Branching Process - Azam Imomov (International Journal of Applied Methods in Electronics and Computers, 2017)
The principal aims are to investigate asymptotic properties of the stochastic population process as a continuous-time Markov chain called Markov Q-Process. We investigate asymptotic properties of the transition probabilities of the Markov Q-Process and their convergence to stationary measures.